THE IDEOLOGICAL MECHANISMS FOR DEVELOPING MORAL IDENTITY AMONG THE YOUTH OF NEW UZBEKISTAN - L. Tashayev (Web of Journals Publishing, 2025)
In recent years, the national identity of the social world has been increasingly challenged by efforts aimed at alienating people from their national consciousness and cultural identity. In such a context, only a nation that glorifies its own identity and national values can deserve genuine respect and recognition. Indeed, a people who remain faithful to their cultural heritage and convey their national traditions and identity to the younger generation without distortion are capable of preserving their name, language, and faith in the world. In this process, the development of self-awareness and identity among youth has become an important and urgent issue.
Keywords: National identity, globalization, national values, national identification, information.